(untitled) (Journal of Applied Learning and Teaching, 2020)
The article situates the challenges that higher education faces before the onset of COVID-19. A future that situates disruptive and immediate transformation for higher education curricula is described to save global universities from the ravages of the “stay-at-home” policies. The move to a totally online environment took place overnight, and most institutions of higher education were totally unprepared. Yet, a future of possibilities could be adopted in the coming five years, one, in particular, being game-based learning, an andragogy based upon experiential education.